KEWENANGAN KEMENTERIAN HUKUM DAN HAM DALAM MENYELESAIKAN TUMPANG TINDIH PERATURAN MENTERI UNTUK MENCAPAI KEPASTIAN HUKUM DI INDONESIA - Moh. Rusydi (Dinamika, 2022)
ABSTRACT               One of the biggest problems in our government today is that there are many laws and regulations issued by the government and these regulations have the potential to be overlapping or disharmony (over legislation,) causing legal uncertainty and slow government wheels. The existence of Permenkum HAM Number 2 of 2019 concerning Settlement of Disharmonization of Legislation through Mediation. The executive has the authority to settle out of court or Non-Judicial Review but whether the status and legal position is in accordance with the existing laws and regulations. because the settlement is within the jurisdiction of the Judiciary, in this case the Supreme Court (MA), then does the government need a special institution to complete laws and regulations such as in South Korea, namely the Minstry of Ligislation (Moleg).Keywords: Authority, Ministry of Law and Human Rights, Legal Certainty.ABSTRAKSalah satu permasalahan terbesar dalam pemerintahan kita hari ini yaitu ada banyaknya peraturan perundang-undangan yang dikeluarkan oleh pemerintah dan peraturan tersebut bepotensi tumpang tindih atau disharmonis (over legislation,) sehingga menyebabkan ketidak pastian hukum dan lambannya roda pemerintahan. Adanya PermenkumHAM Nomor 2 Tahun 2019 tentang Penyelesaian Disharmonisasi peraturan Perundang-undangan Melalui Mediasi. Eksekutif mempunyai kewenangan dalam menyelesaikan diluar pengadilan atau Non-Judicial Review tapi apakah status dan kedudukan hukum  tersebut sesuai dengan peraturan perundang-undngan yang ada. karena penyelesaian tersebut merupakan wilayahnya Yudikatif dalam hal ini Mahkamah Agung (MA) lalu apakah pemerintah perlu lembaga khusus untuk meyelesaiak peraturan perundang undangan seperti di di Korea Selatan yakni Minstry of Ligislation (Moleg).Kata Kunci : Kewenangan, Kementerian Hukum dan HAM, Kepatian Hukum.